Allele-specific DNA identity patterns. - Wainscoat, J; Pilkington, S; Peto, T; Bell, J; Higgs, D (Springer-Verlag, 1987)
A method of genetic analysis is presented which involves digestion of DNA with a single restriction enzyme (PvuII) and hybridisation with a mixture of five probes. Four of the five probes chosen recognise hypervariable regions (HVRs) of the human genome and hence an allele-specific DNA identity pattern results. An advantage of this approach to genetic characterisation is that the complex identity patterns may be broken down into simple allelic systems of known chromosomal localization by hybridisation with the individual probes. Also different probes may be included in a combined probe designed for particular types of investigation.